Tinjauan Sistematis : Efektivitas Kapsul Ikan Gabus (Channa striata) terhadap Peningkatan Kadar Albumin pada Pasien Hipoalbuminemia - Putu Alin Michelle Arisanti; Rini Noviyani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Hypoalbuminemia is an abnormal condition indicated by low albumin levels, which is <3.5 g/dL and is commonly found in patients with chronic diseases. Conventional therapy through Human Serum Albumin (HSA) is often an option, but has limitations, including fornas restrictions, very high costs, and limited availability. Thus, other more effective and efficient alternatives are needed, namely by utilizing biological sources such as snakehead fish in the form of supplements or capsules. Although there have been various studies and clinical evidence regarding its effectiveness, literature reviews that tabulate the results of various studies are still very limited. Therefore, this systematic review needs to be written to determine the effectiveness of administering snakehead fish capsules on albumin levels in patients with hypoalbuminemia. The compilation of this literature review uses a literature review method that is presented descriptively using several databases that meet the inclusion and exclusion criteria that have been set. The final result obtained 12 literatures that met the inclusion criteria for further study. The results of the review consistently showed that capsules or supplementation of snakehead fish extract were proven to be significantly effective in increasing albumin levels in patients. Factors that influence the effects of administering snakehead fish capsules are the dose and frequency of administration. It was revealed that intervention for 21 days provided superior albumin increase results compared to a duration of 10-14 days. This finding is very relevant because it is in accordance with the biological half-life of albumin in the liver, which is around 21 days. This literature review is expected to be a strong scientific basis for further research and the development of more effective clinical policies in the future.